Kampus Merdeka: College Educational Breakthrough to Address the Wide Gap Between Industry and Academia - Kusumo, Haryo; Solechan, Achmad; E. Caingcoy, Manuel; Marlina, Dian; Novita, Mega (KnE Social Sciences, 2022)
Kampus Merdeka was part of the Merdeka Belajar policy released by the Indonesian Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) at the end of January 2020. This study focuses on a university program that gave students opportunities to develop skills in accordance with their talents and interests by entering the workforce right away as training for future careers. Until the middle of September 2022, 12 programs had launched. To provide a reliable reference, a comprehensive analysis of the Merdeka Curriculum program was carried out in this work. We took a qualitative approach, conducting observations and interviews with fellow actors as well as a thorough analysis of pertinent databases on the related subjects. We found that active student participation and support from the university are the keys to the success of Kampus Merdeka. Furthermore, serious commitment is needed from all parties to gain a company’s trust. This study is important to gain deep insights into the Kampus Merdeka policy so that the needs of Kurikulum Merdeka can be met effectively. Keywords: independent curriculum; Kampus Merdeka, industry-academic collaboration